Perencanaan peta tata guna lahan Kecamatan Sematang Borang - Rahmadani, Risqina Raya; Dewi, Anggi Purnama Sari (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Land use refers to an organized spatial management pattern through institutional arrangements for the benefit of the community in a fair manner. Land use maps serve as an analysis tool that helps determine the area of the area, monitor development, and identify land use patterns. This study aims to produce land use map planning in Sematang Borang District by utilizing manual measuring devices and GPS. The research method used by the Focus Group Discussion (FGD) method was used to obtain additional information from related agencies. The process of planning land use maps in Sematang Borang District begins with the identification of problems and regional objectives, followed by field surveys to collect primary and secondary data. The results will be a reference for more targeted and sustainable land use policies. The results of the land use map planning research comprehensively describe the allocation of space for various functions, such as settlements, industries, green open spaces, and conservation. Environmental, social, and economic aspects are the main focus in this planning, with the aim of supporting sustainable management of the area. The environmental aspect pays attention to the sustainability of natural resources and ecosystem protection, while the social aspect emphasizes an inclusive approach to local communities for well-being.